2013
DOI: 10.1302/0301-620x.95b3.29456
|View full text |Cite
|
Sign up to set email alerts
|

New polyethylenes in total hip replacement

Abstract: Between 1999 and 2001, 90 patients underwent total hip replacement using the same uncemented acetabular and femoral components with a 28 mm metallic femoral head but with prospective randomisation of the acetabular liner to either Durasul highly cross-linked polyethylene or nitrogen-sterilised Sulene polyethylene. We assessed 83 patients at a minimum follow-up of ten years. Linear penetration of the femoral head was estimated at six weeks, six and 12 months and annually thereafter, using the Dorr method, given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 50 publications
4
37
0
Order By: Relevance
“…However, the RSA measurements also indicated migration and rotation of the components after 7 years. Garcia-Rey et al [11] reported the minimum 10-year results of a randomized trial of uncemented hips with 42 Durasul XLPE (Zimmer) and 41 Sulene conventional polyethylene (Zimmer) liners. All femoral heads were 28 mm but fabricated of stainless steel in the Sulene group and cobalt-chrome in the Durasul group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the RSA measurements also indicated migration and rotation of the components after 7 years. Garcia-Rey et al [11] reported the minimum 10-year results of a randomized trial of uncemented hips with 42 Durasul XLPE (Zimmer) and 41 Sulene conventional polyethylene (Zimmer) liners. All femoral heads were 28 mm but fabricated of stainless steel in the Sulene group and cobalt-chrome in the Durasul group.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study using the titanium fiber-metal acetabular component and this XLPE showed low linear wear and no osteolysis at 5 to 8 years followup, but there was more volumetric wear in those hips with 36-and 40-mm femoral heads [15]. There are few studies of XLPE with 10-year followup time, but these are limited by small numbers of patients and different wear measurement techniques [1,8,11,13,25]. To our knowledge, there are no studies using the measurement method described by Martell of the linear and volumetric wear of electron beam 10-kGY remelted polyethylene and the presence of osteolysis at a minimum followup of 10 years.…”
Section: Introductionmentioning
confidence: 91%
“…None of the patients required revision surgery or had evidence of osteolysis or loosening. The remaining 10-year followup studies include patients with a mean age greater than 50 [2,4,12,14,17,21,37].…”
Section: Discussionmentioning
confidence: 99%
“…Eighty hips had the same diameter head (28 mm) allowing us to more accurately compare the different bearing materials. The type of femoral head used was related to our sequential use of materials beginning with cobalt chrome (14), ceramic (23) followed by Oxinium (43) in the hips with 28-mm heads. Although cobalt-chrome was used early in this study, our previous experience with ceramic on polyethylene encouraged us to use it as an alternative bearing.…”
mentioning
confidence: 99%
“…At both stages of selection, we estimated chance-adjusted agreement statistics among reviewers with a j statistic (j = 0.917 for abstract review; j = 1.000 for full-text review), and all disagreements were settled by the opinion of a third senior reviewer (GAN-M). Eleven articles [2,4,5,8,14,22,28,33,40,41,49] were deemed eligible through this process and seven studies [9,[16][17][18][19][20][21] were added following a manual search of the bibliographies of the 11 chosen articles for a final study cohort of 18 manuscripts (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%